Evaluation of Drying Air Conditions for Antiozonant Wax Drying Process in the Spray Drying Tower - Marcelinus Christwardana; Ifa Miftahushudury (Department of Chemical Engineering, Universitas Gadjah Mada, 2021)
The drying technique of Antiozonant Wax (AOW) using drying air in the spray drying tower has a considerable effect on the produced AOW powder. In this study, the drying air flow rate was measured in such a way that AOW can transform into a powder with a size of 800 mesh. The diameter and height of the spray drying tower are 1 and 6 m, respectively. Meanwhile, the AOW flow rate to the spray drying tower varies from 100 kg/hour to 500 kg/hour. The intake AOW temperature was 70 °C and at the outlet was 40 °C, while the drying air temperatures in and out of the spray drying tower were 30 and 55 °C, respectively. From the calculation results, the flow rate of the drying air is directly proportional to the flow rate of the AOW into the spray drying tower but inversely proportional to the speed of the AOW powder down the spray drying tower. In the meantime, the drying period for AOW to become a powder is between 1.033 – 1.279 s, not significantly different. It gives insight into the need to dry air in the spray drying tower configuration so that the findings will conform to the predetermined requirements.